Undergraduate Novice Researchers’ Experiences in Conducting Mini-Research in Education: Kolb Learning Cycle - Adaninggar Septi Subekti (Universitas Jambi, Indonesia, 2020)
This study investigated eight pre-service English teachers’ first experiences in conducting mini-research analyzed using four stages of Kolb Experiential Learning Cycle, consisting of Concrete Experience (CE), Reflective Observation (RO), Abstract Conceptualisation (AC), and Active Experimentation (AE) stages. It was conducted to fill the void in studies in the area of research methods instruction in the English as Second Language (ESL) context. The study used qualitative analysis on secondary data in the forms of student reflections. Through Thematic Analysis, this study found five themes. From three themes of experiences, it was found that the participants’ experiences were mainly in the first three stages of the cycle, CE, RO, and AC. Only two of the five themes suggested that the participants had achieved, to certain extent, AE stage, characterized with decision-making and problem solving, which may be attributed to the participants’ being beginner researchers who still needed more experiences in research.